Pengaruh Jenis Kelamin, Pendidikan, dan Pendapatan Masyarakat terhadap Kesediaan Membayar atau Willingness To Pay (WTP) Mobil Listrik di Surakarta - Elvira Wahyu Arum Fanani; Husin Bugis; Nugroho Agung Pambudi; Muhammad Kunta Biddinika (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
Indonesia has an ambitious national energy goal of developing electric vehicles (EVs). Electric vehicles can be a solution to reduce energy consumption and carbon dioxide emissions in the transportation sector. So this research has an important role in directing the right policies to realize these targets. This study aims to analyze the factors that influence the people of Surakarta to buy an electric car. The research sample is the people of Surakarta as many as 348 people. The test results were analyzed using multiple linear regression method with analysis using SPSS version 25. The results of this study indicate that gender, education level, and people's income affect the willingness to buy electric cars. These factors together have an effect of 16.5% on the willingness to pay for an electric car. In addition, the average WTP value for purchasing electric cars is estimated to be around Rp. 179,885,058.00.